A City in Transition – Venice in the Late 18th Century (KULT_online, 2013)
The 18th century was for Venice a period of flourishing cultural production as well as social changes which are discussed in many literary works. In a study worth the reading, Robert Fajen analyses the Venetian literature published in the late 18th century and describes the changes concerning the perception of the Venetian people by themselves and by foreigners. The author seeks to explain the growing tensions in the Venetian society of the time. In addition, he discusses the state of research on Carlo Goldoni.